PEMBERDAYAAN MASYARAKAT DESA BASSEANG MELALUI PELATIHAN PEMBUATAN SAUS CABAI SEBAGAI PRODUK UNGGULAN LOKAL - Hikmahwati, Hikmahwati; Afni, Nur; Dalima, Dalima; Cahyanti, Ice; Rezky, Ainur; Akbar, Muh Rizky; Tahang, Sunardi; Firdaus, Muhammad; Nacing, Nursyawal; Suharman, Suharman; ilmi , Nur (Ininnawa : Jurnal Pengabdian Masyarakat, 2025)
The community service program in Basseang Village was conducted to enhance local residents’ skills and self-reliance in processing agricultural products into high-value commodities, particularly through training on chili sauce production. This activity aimed to address the low market price of fresh chili during harvest seasons and to encourage the development of small-scale, home-based food enterprises. In addition, the program introduced the production of trichocompost as an environmentally friendly organic fertilizer, utilizing Trichoderma sp. as a biostimulant to accelerate the decomposition of organic materials such as goat manure and crop residues. The resulting compost was later applied to support organic chili cultivation as the main raw material for sauce production.The program was implemented through socialization, hands-on training, and direct mentoring involving women’s groups and young farmers. Evaluation results indicated that participants were able to produce chili sauce independently, with a comprehension rate of 90%. Meanwhile, the use of trichocompost helped reduce agricultural waste and improve soil fertility. Overall, this activity positively impacted household income, fostered entrepreneurial awareness, and promoted the application of appropriate technology to support sustainable agricultural practices in Basseang Village.